High-yield production of a super-soluble miniature spidroin for biomimetic high-performance materials. (November 2021) - Schmuck, Benjamin; Greco, Gabriele; Barth, Andreas; Pugno, Nicola M.; Johansson, Jan; Rising, Anna
Graphical abstract: Abstract: The mechanical properties of artificial spider silks are approaching a stage where commercial applications become realistic. However, the yields of recombinant silk proteins that can be used to produce fibers with good mechanical properties are typically very low and many purification and spinning protocols still require the use of urea, hexafluoroisopropanol, and/or methanol. Thus, improved production and spinning methods with a minimal environmental impact are needed. We have previously developed a miniature spider silk protein that is characterized by high solubility in aqueous buffers and spinnability in biomimetic set-ups. In this study, we developed a production protocol that resulted in an expression level of >20 g target protein per liter in an Escherichia coli fed-batch culture, and subsequent purification under native conditions yielded 14.5 g/l. This corresponds to a nearly six-fold increase in expression levels, and a 10-fold increase in yield after purification compared to reports for recombinant spider silk proteins. Biomimetic spinning using only aqueous buffers resulted in fibers with a toughness modulus of 74 MJ/m 3, which is the highest reported for biomimetically as-spun artificial silk fibers. Thus, the process described herein represents a milestone for the economic production of biomimetic silk fibers for industrial applications.